Contract Duration and Indexation in a Period of Real and Nominal Uncertainty - Louis Christofides; Amy Chen Peng (Center for Economic Studies and ifo Institute (CESifo), 2003)
A sample of 11885 wage agreements, reached in the Canadian unionized sector during 1976-2000, a period of high as well as exceptionally low inflation and substantial fluctuations in nominal and real uncertainty, is used to study the determinants of key provisions of contracts such as their duration and indexation clauses. Econometric techniques, which account for the interaction between duration and indexation, as well as the latent nature of the elasticity of indexation are used. Results obtained suggest that expected inflation, nominal and real uncertainty account for most of the secular and cyclical changes in contract provisions.
Keywords: 330; contract duration; indexation; nominal; real uncertainty